2020
DOI: 10.1371/journal.pone.0226580
|View full text |Cite
|
Sign up to set email alerts
|

Female finches prefer courtship signals indicating male vigor and neuromuscular ability

Abstract: Female songbirds use male song to discriminate among individuals and evaluate their quality as potential mates. Previous behavioral experiments in many species, including the species studied here, have shown that females will solicit copulation in response to song even if no male is present. Those data demonstrate that female mate choice is closely tied to song features, but they leave open the question of which song parameters are most influential in female mate selection. We sought to identify features of ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 51 publications
(88 reference statements)
2
16
0
Order By: Relevance
“…Regardless of the developmental mechanism of preference for the father’s song, our results together with previous reports of song preference in female Bengalese finches measured by other behavioral responses (e.g., operant conditioning, phonotaxis, and vocalizations) [ 14 , 15 ] imply the importance of considering individual variations in female song preference in this species. In previous studies, researchers have explored acoustical and temporal song characteristics that are preferred across individuals in female Bengalese finches [ 14 , 52 – 54 ]. For example, in a call-back assay experiment where song tempo or pitch were manipulated, the authors found that the majority of females preferred faster songs while changes in pitch were not a good predictor of female response [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of the developmental mechanism of preference for the father’s song, our results together with previous reports of song preference in female Bengalese finches measured by other behavioral responses (e.g., operant conditioning, phonotaxis, and vocalizations) [ 14 , 15 ] imply the importance of considering individual variations in female song preference in this species. In previous studies, researchers have explored acoustical and temporal song characteristics that are preferred across individuals in female Bengalese finches [ 14 , 52 – 54 ]. For example, in a call-back assay experiment where song tempo or pitch were manipulated, the authors found that the majority of females preferred faster songs while changes in pitch were not a good predictor of female response [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most simply, this might include variation in the temporal dynamics of other movements; however, it likewise could include variation along any axis of behavior that is influenced by changes to the synaptic strength or excitability within underlying neural circuitry. This is especially interesting from the perspective that song is a courtship behavior that female birds use in part to select their mates ( 17, 20 ). The joint influences of experience and heritability on tempo render it an informative signal about the relatedness of the singer ( 77, 78 ), while the possibility that other behavioral traits covary with tempo suggests that It might additionally provide females with signals about inter-individual differences that are relevant to assessment of a male’s fitness and compatibility.…”
Section: Discussionmentioning
confidence: 99%
“…Birdsong-a complex motor skill acquired through cultural transmission and subserved by well-delineated neural circuitry (7)(8)(9)(10)-offers an attractive model for studying heritable sources of variation in learned behavior. In particular, song tempo-a defining characteristic of the male's courtship song and motor skill performance more generally (11)(12)(13)(14)(15)(16)-is shaped both by experience during learning from a tutor and by heritable factors (17)(18)(19)(20)(21)(22)(23). Moreover, while the characteristic tempo at which an adult bird sings varies by only a few percent from day to day, the tempos at which different individuals sing can span more than a factor of two (11,13,22).…”
Section: Main Textmentioning
confidence: 99%
“…Regardless of the developmental mechanism of preference for the father's song, our results together with previous findings [14,15] imply the importance of considering individual variations in female song preference in the Bengalese finch. In previous studies on this species, researchers have explored acoustical and temporal song characteristics that are preferred across individuals [14,[38][39][40]. For example, in a call-back assay experiment where song tempo or pitch were manipulated, the authors found that the majority of females preferred faster songs while changes in pitch were not a good predictor of female response [38].…”
mentioning
confidence: 99%
“…In previous studies on this species, researchers have explored acoustical and temporal song characteristics that are preferred across individuals [14,[38][39][40]. For example, in a call-back assay experiment where song tempo or pitch were manipulated, the authors found that the majority of females preferred faster songs while changes in pitch were not a good predictor of female response [38]. There are other studies that are especially relevant to the characteristics of Bengalese finch song and its evolutionary process.…”
mentioning
confidence: 99%